Ethnobotanical study on medicinal plants used by ethnics of Bajau Ubian and Dusun Bonggi on Southern part of Banggi Island, Kudat / Fatin Afinah Abdul Rahman - Abdul Rahman, Fatin Afinah (Faculty of Applied Sciences, Universiti Teknologi MARA Sabah, 2017)
Generally, the ethnobotanical study emphasizes on the relationship of specific ethnicity and plants in various aspect of life such as medicinal, clothing, furnishers, textile, currency, cosmetic, ornamentation, and religious ceremony. This ethnobotanical study is specifically focus on medicinal purpose used by the ethnics of Bajau Ubian and Dusun Bonggi on southern part of Banggi Island that located under sub-district of Kudat. The study was conducted through interviews by several intensive visiting started on end of July 2016 to early of September 2016. A total of 47 species of medicinal plants was noted and collected. These medicinal plants are come from 27 family namely Acanthaceae, Annonaceae, Apiaceae, Arecaceae, Asteraceae, Bigoniaceae, Bombacaceae, Cyperaceae, Euphorbiaceae, Fabaceae, Fagaceae, Iridaceae, Lamiaceae, Malvaceae, Menispermaceae, Myrtaceae, Moraceae, Musaceae, Poaceae, Piperaceae, Pandanaceae, Rutaceae, Ulmaceae, Solanaceae, Sterculiaceae, Verbenaceae, and Zingiberaceae. As for preparation method, most of these medicinal plants are being boiling and combined with other ingredients, and the part used includes rhizome, leaves, stem, bark tree, and thorn. These medicinal plants are claimed can treated 14 categories of disease such as dermatologic disease, gastrointestinal diseases, menstrual disorder, postnatal care, periodontal diseases, pulmonary system disease, and so on.